An Analysis of Field Preferences of an Educational System - Ćwiąkała-Małys, Anna; Mościbrodzka, Monika (University of Wroclaw. Faculty of Law, Administration & Economics, 2019)
It is the labour market that decides about the popularity of a field of studies. The area where the highest number of job offers appears is reflected in the offers of universities. However, it is very often mentioned in many media that future students decide to choose social and humane studies whose market chances are evaluated on a relatively low level.
Keywords: szkolnictwo wyższe; syntetyczny wskaźnik rozwoju; metody analizy wielowymiarowej